Paweł Nowicki, Axiology of public procurement law. Between economic efficiency and instrumentalization, Towarzystwo Naukowe Organizacji i Kierownictwa, Stowarzyszenie Wyższej Użyteczności „Dom Organizatora”, Toruń 2019, pp. 407 - Kowalczyk, Ewaryst (Studia Iuridica Toruniensia, 2020)
The monograph Axiology of public procurement law by dr Paweł Nowicki is an example of a publication that is part of the general current research on the axiology of law. However, the issue of values in public procurement in general has not been intensively considered in Poland until now. It appeared most often as part of studies on separately analyzed issues of public procurement, including those related to the principle of fair competition, the principle of transparency and social or environmental aspects of public procurement. The author describes his research intentions as an attempt to identify the objectives of public procurement law in general. In accordance with his declaration, the author accomplished his task by analyzing source material, taking into account both EU public procurement law standards and national regulations. The conclusion of Dr. N owicki’s research indicates the complex nature of public procurement objectives, including not only purchasing functions, but also serving the implementation of specific values, including, e.g. fairness in competition, sustainable development or legal compliance. The author of Axiology thus presented the view that public procurement law ex natura implements many, not mutually exclusive, although serving different value goals.